2001
DOI: 10.1002/1522-2683(200102)22:3<586::aid-elps586>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of cultivar-specific interactions betweenRhizobium leguminosarum biovartrifolii and subterranean clover cultivar Woogenellup

Abstract: Proteome analysis was used to identify proteins that are involved in the early stages of nodulation between the subterranean clover cultivar Woogenellup and the Rhizobium leguminosarum bv. trifolii strains ANU843 and ANU794. Strain ANU843 induces nitrogen-fixing nodules whereas strain ANU794 forms aberrant nodules on the roots of cv. Woogenellup that fail to develop beyond an early stage. Our aim was to identify proteins that might be involved in the early stages of nodulation over a 48 h period and to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 41 publications
1
44
0
2
Order By: Relevance
“…This study revealed over 250 proteins induced or up-regulated upon infection, which were mainly of bacterial origin present in the nodules as compared with the roots. Other studies followed, such as that reported by Morris and Djordjevic [73] and more recently by Miché et al [74] and van Noorde et al [75], in which proteins involved in rootbacteria interaction were identified. These data reinforce the importance of the study of roots for the discovery of resistance-related genes and proteins in plants.…”
Section: Root-bacteria Interactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…This study revealed over 250 proteins induced or up-regulated upon infection, which were mainly of bacterial origin present in the nodules as compared with the roots. Other studies followed, such as that reported by Morris and Djordjevic [73] and more recently by Miché et al [74] and van Noorde et al [75], in which proteins involved in rootbacteria interaction were identified. These data reinforce the importance of the study of roots for the discovery of resistance-related genes and proteins in plants.…”
Section: Root-bacteria Interactionsmentioning
confidence: 96%
“…The protocols employed to study the nodule proteome are quite diverse, but they have generally recurred to differential centrifugation steps. Recently, this type of procedure has been demonstrated in proteomic studies of M. trunculata root nodules infected by Agrobacterium tumefaciens [28], in soybean root nodules infected by Bradyrhizobium japonicum [29], in pea root and Woogenellup roots infected by Rhizobium leguminosarum [30,31], in Lotus japonicus root nodules infected by Mesorhizobium loti [32]. Furthermore, the characterization of membrane-associated proteins has also been possible with an additional chloroform/methanol extraction step, as demonstrated in the comparative proteomic study of M. truncatula roots inoculated with the fungus Glomus intraradices [33].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Through proteomic analysis, several studies have reported identification of symbiosis-related proteins in various plant materials: root and root hairs, [11][12][13][14] nodules, [14][15][16] the peribacteroid membrane, 17,18) nodule mitochondria, 19) the nodule cytosol, 20) xylem, 21) and apoplast. 21) However, most of these studies focused on the protein profile of the specific organelle or tissue at a defined time point, especially at the early stage of nodulation, and development of indeterminate nodules.…”
mentioning
confidence: 99%
“…Similar tools were used to identify symbiosis-related proteins in M. truncatula (BestelCorre et al, 2002). Two special studies (Natera et al, 2000;Morris and Djordjevic, 2001) were devoted to the analysis of changes in protein expression in bacteroids compared with free bacteria, and in nodules compared with uninfected roots. Numerous changes were observed representing mostly abundant proteins of known function (like malate dehydrogenase [MDH], DNAK, GroEL, and leghemoglobin).…”
mentioning
confidence: 99%
“…Numerous changes were observed representing mostly abundant proteins of known function (like malate dehydrogenase [MDH], DNAK, GroEL, and leghemoglobin). After inoculation of roots with Rhizobium leguminosarum bacteria, 10 developmentally regulated proteins were identified including ␣-fucosidase, ethylene-induced proteins, tubulin, and chaperonin 21 (Morris and Djordjevic, 2001). The results of such studies have demonstrated that proteomics is a powerful tool to gain insight into the expression, abundance, and distribution of proteins in special tissues of model legumes.…”
mentioning
confidence: 99%